Strengthening Local Wisdom through Extracurricular Activities: Integrated Islamic Education in Banda Aceh - Cut Nyak Marlina; Salami Mahmud; Sehat Ihsan Shadiqin; Syatria Adymas Pranajaya; Sy. Rohana; Fatmawati Fadli (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2026)
The development of Integrated Islamic Elementary Schools (SDIT) in Banda Aceh reflects the diverse dynamics of efforts to integrate national education, Islamic values, and local wisdom in Aceh. However, studies specifically examining the process of strengthening local wisdom through extracurricular activities in integrated Islamic education remain limited. This study aims to deeply examine the transformation of strengthening Acehnese local wisdom through extracurricular activities and reveal the characteristics and advantages of implementing integrated Islamic education in SDITs in Banda Aceh. The study employed a descriptive qualitative approach using a case study method at three Integrated Islamic Elementary Schools (SDIT); SD Islam Al-Azhar Cairo Banda Aceh, SDIT Nurul Ishlah Banda Aceh, and SDIT Quantum School Aceh. Data were collected through observation, semi-structured interviews, and document analysis, and were then analyzed using the Miles and Huberman model with triangulation techniques to ensure validity. The results of the study demonstrate that extracurricular activities play a pivotal role in reinforcing and enhancing the values of Aceh's Islamic-based local wisdom. These values include Islamic manners, discipline, unity, responsibility, social awareness, and a love for Aceh's Islamic culture. This transformation occurs contextually through habituation, educators' examples, and direct learning experiences. Additionally, integrated Islamic education in Banda Aceh has developed adaptively and is not homogeneous. Each SDIT has different characteristics and strengths, ranging from integrating technology and memorizing the Qur'an to adopting the multiple intelligences approach. These findings confirm that strengthening local wisdom through extracurricular activities is an effective, sustainable strategy for shaping students' religious and cultural identities. This strategy can be adapted and applied in different contexts without losing the fundamental values of Islam and local wisdom. This makes it relevant for addressing the challenges of basic education in the modern era.